Advancing local helicity injection for non-solenoidal tokamak startup. (22nd May 2019) - Bongard, M.W.; Bodner, G.M.; Burke, M.G.; Fonck, R.J.; Pachicano, J.L.; Perry, J.M.; Pierren, C.; Reusch, J.A.; Rhodes, A.T.; Richner, N.J.; Rodriguez Sanchez, C.; Schaefer, C.E.; et al.
Abstract: Experiments on the Pegasus ST are advancing the physics and technology basis of local helicity injection (LHI). LHI injects helicity with relatively intense electron current sources in the plasma edge. It creates high toroidal current, toroidally-averaged tokamak-like plasmas that have been efficiently transitioned to Ohmically driven tokamak plasmas. Tradeoffs between physics and engineering goals are tested with LHI systems on the low-field-side and the high-field-side of Pegasus, producing plasmas predominantly driven by non-solenoidal induction and DC helicity drive, respectively. An extensive LHI source development campaign comparing active arc sources, passive and gas-effused electrode sources lead to the selection of active arc sources for present and next-step LHI deployments. LHI plasmas with net toroidal current MA, eV, and m −3 are attained to date. A predictive 0D power-balance model describes experimental and partitions the active current drive sources. High-frequency MHD activity is found to be present during LHI current drive, in addition to modes previously found in NIMROD simulation and experiment. A new regime of reduced MHD activity was discovered where activity is suppressed, LHI CD efficiency improves, and long-pulse plasmas are sustained with .